Developments in current game-based learning design and deployment - Felicia, Patrick (Premier reference source, 2013)
"This book highlights the latest research from professionals and researchers working in the fields of educational games development, e-learning, multimedia, educational psychology, and information technology, promoting an in-depth understanding of the multiple factors and challenges inherent to the design and integration of game-based learning environments" - Provided by publisher